Why do Parents Underinvest in their Children's Education? Evidence from China - Jiyuan Wang; Rob Alessie; Viola Angelini (Global Labor Organization (GLO), 2022)
In this paper we study whether the presence of binding liquidity constraints and the existence of fixed costs can explain the underinvestment of parents in their children's human capital. We first incorporate these two potential mechanisms into the theoretical model of Raut & Tran (2005) and then we test their empirical relevance using data from the China Health and Retirement Longitudinal Study (CHARLS). Our results show that especially fixed costs play an important role in explaining human capital underinvestment.
Keywords: J24; J31; I2; 330; Two-Sided Altruism; Human Capital; Liquidity Constraints; Fixed Costs